Impact Evaluation of Ayurveda Outreach Clinic for the Management of Non- Communicable Diseases Program in Nepal - Bhusal, Nirmal; Sapkota, Suprich; Upadhyay, Vasudev; Thakur, Siddhartha; Panthi, Sarad (Tribhuvan University Journal, 2024)
Department of Ayurveda and Alternative Medicine (DOAA), one of the departments of the Ministry of Health and Population (MOHP), manages Ayurveda and alternative medicine services and promotes health through Ayurveda health institutions across the country. The department also carries out planning, programming, coordination, supervision, monitoring of Ayurveda service programs. Ayurveda Outreach clinic for the management of non-communicable diseases (NCDs) is a major program which focuses on the preventive aspect of health care and aims to develop and promotes a healthy lifestyle in people and tries to prevent and manage NCDs. This program is being delivered from Ayurveda hospitals, Ayurveda health centres and outreach clinics (ORC). The key activities are to provide the Ayurveda health services to the unreached population. General health check-up and medicine distribution were the main activities of the ORC. The ORC mainly served elderly women and poor people. High blood pressure, gastritis, asthma, osteoarthritis, rheumatoid arthritis, gouty arthritis and constipation were the chief health complaints of the people. The activities of the program are relevant to bring notable changes in the community as people who visit the ORC site are being informed about the health and Ayurveda and are also receiving the quality services. Provision of Snehana and Swedena in some places has increased the utilization of the health services and the activities of the program have been performed effectively to bring the desired result to prevent and manage the NCDs.